Meeting Cheikh Anta Diop on the Road to African Resurgence. Issue 1 (2nd January 2018) - Asante, Molefi K.
Abstract: The African people's relentless struggle to tell their own stories and take charge of their own historical languages is a prerequisite for achieving an African Renaissance. This argument, informed by Afrocentricity—a theoretical framework which advances the view that any examination of African issues must be informed by African history and culture—takes its cue from the great Senegalese Pan-Africanist and African Renaissance advocate, Cheikh Anta Diop. The year 2018 marks 70 years since Diop, at a tender age of 25, wrote his essay When will we be able to speak of an African Renaissance? On the occasion of the 70th anniversary of this article, it is appropriate that the African Renaissance project advocates take a moment and deeply reflect on how they can take African scholarship to higher levels and intensify and consolidate the struggle to liberate Africa from being preoccupied with the Eurocentric trajectory of privileging Europe and Europeans in all aspects of life—the intellectual, political, cultural, social and material. This article argues that embracing Africology—the Afrocentric approach to scholarship—is the first step towards the liberation of a scholarship project. Diop dedicated his life to using sciences—both the natural and social sciences for the liberation of Africa and humankind—to liberate Africans from inferiority complex, and Europeans from superiority complex. Although Diop recognised both the importance of science and ideology in the service of humanity, he drew a line between them.